Preparation, Characterization and Activity of Ni and N co-doped TiO2 Photocatalyst in Degradation of Methylene Blue - Priatmoko, S.; Triyono; Kartini, I.; Roto (Asian Journal of Chemistry, 2016)
Preparation of Ni and N co-doped TiO2 photocatalyst using sol-gel method with precursors titanium isobutoxide, nickel nitrate and urea, respectively as a source of titanium, nickel and nitrogen have been done. Photocatalyst were characterized using X-ray diffraction, spectroscopy UV-visible diffuse reflectance, scanning electron microscopy, FTIR spectroscopy. Photocatalytic activity was tested against the degradation of methylene blue using visible light from xenon lamp 300 watt. The results showed that on the TiO2 co-doped Ni and N indicates that encouragement the concentration of Ni (at fixed concentration of N), causing an increase in crystallite size. While on boosts concentration N (at fixed concentrations of Ni) initially provides enhanced crystallite size and reaches a maximum at certain composition. Addition of a single dopant Ni and N decrease the band gap energy of TiO2 and obtained the lowest value of each successive 3.080 and 3.093 eV. The addition of double dopant Ni and N are generally lowers the band gap energy of TiO2. The activity of the Ni-N-TiO2 photocatalyst showed the optimum time degradation in the 90th min with a degradation rate of approximately 80 % obtained in the photocatalyst with composition % mol ratio of Ni:N = 2.5: 2.5.